Optimal Impedance Control with TSK-type FLC for Hard Shaking Reduction on Hydraulically Driven Hexapod Robot - Addie Irawan, Hashim; Nonami, Kenzo; Mohd Razali, Daud (Springer, 2013)
This article presents the strategy of control to improve the performance of applied impedance control in hydraulically driven hexapod robot named COMET-IV, during walking/operating on various type of extremely uneven terrain. The robot’s body moment of inertia is calculated and adapted as impedance control feedback and the Sugeno type fuzzy or so called Takagaki-Sugeno-Kang Fuzzy Logic (TSK-FLC) with Linear Quadratic Regulation (LQR) based gain tuning is cascaded for optimization purposes. The proposed control strategy is verified in the actual robot system with walking on the setup extremely uneven terrain in the laboratory.